PERANCANGAN SISTEM E-KATALOG CEMERLANG KOMPUTER DENGAN PENDEKATAN METODE RAD - Qisthiano, M Riski; Imron, Ali (Journal of Information Systems Management and Digital Business, 2024)
The rapid development of information and communication technology has encouraged Cemerlang Computer, a company that provides services in the fields of hardware, maintenance, hardware repair, as well as applications and software, to continue to innovate. This research discusses the design of the Cemerlang Computer e-catalog system using the Rapid Application Development (RAD) method. This approach is expected to provide a competitive advantage by leveraging the development speed and flexibility of RAD. The e-catalog design process is focused on increasing the company's responsiveness to market changes, improving service quality, and strengthening customer interactions with products and services. This research describes in depth the RAD implementation process, providing a comprehensive understanding of the stages of its implementation, as well as its potential in optimizing the company's operational efficiency. The research results are expected to provide practical guidance for Cemerlang Computer in implementing adaptive e-catalog solutions, improving user experience, and responding to the dynamics of the information technology industry which continues to develop. Thus, this research contributes to a better understanding of e-catalog system design strategies that can be implemented by similar companies in facing the current digital era